SCHOOL-TO-WORK TRANSITION FOR STUDENTS WITH SPECIAL NEEDS: A SYSTEMATIC REVIEW - Jamaludin, Ainor Salikin; Abd Aziz, Nurbieta; Nor Azmi, Nadhirah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
The transition from school to employment remains a persistent challenge for students with special needs, with many experiencing fragmented supports, limited access to authentic work experiences, and uneven post-school outcomes despite policy attention and expanding transition initiatives. This systematic literature review (SLR) addresses the problem of scattered and rapidly growing evidence by synthesising recent empirical studies to clarify what is currently known and where critical gaps remain in supporting school-to-work transition for this population. Following the PRISMA protocol, an advanced search was conducted in two databases (Scopus and ERIC) using the keywords “transition to work”, “students” and “special needs”, with publication years limited to 2022–2025. After screening and eligibility assessment, 35 primary studies (n = 35) were included for analysis and thematic synthesis. Numerical results indicate that the reviewed evidence clustered into four dominant themes: (1) Pre-Employment Transition Services and Vocational Rehabilitation Systems (Pre-ETS/VR), (2) Work-Based Learning, Apprenticeship, and Community/Employer Pathways, (3) Psychosocial Readiness, Aspiration, Motivation, and Career Development, and (4) Contextual and Ecological Barriers, Inclusion, and Structural Transition Challenges. Across these themes, findings commonly emphasised the importance of coordinated interagency services, meaningful employer-linked learning, strengthened career self-determination, and mitigation of structural barriers that restrict participation and inclusion. Overall, the synthesis suggests that effective transition support is multi-component and context-sensitive, requiring integration of service systems, sustained workplace-based opportunities, and family, school and community collaboration. This review concludes that future research and practice should prioritise scalable models with clear implementation guidance, strengthen equity-driven supports for diverse learners, and evaluate longer-term post-school outcomes to move beyond short-term indicators of readiness and participation.